Wenlock and Pridoli (Silurian) crinoids from Saaremaa, western Estonia (Phylum Echinodermata). (9th March 2015) - Ausich, William I.; Wilson, Mark A.; Vinn, Olev
Abstract: Study of new collections of the Wenlock and Pridoli, Silurian, crinoids from Saaremaa, western Estonia, result in taxonomic revision, expanded ranges, and new taxa. Eucalyptocrinites regularis and Periechocrinus laevis are recognized outside of Sweden for the first time. Desmidocrinus laevigatus Ausich et al., 2012 is reassigned to Methabocrinus . Because the type species of Methabocrinus was previously known only from glacial sediments, the age and provenance of this genus are constrained for the first time. A new crotalocrinitid, Velocrinus coniculus new genus and species, is described. Although the Pridoli faunas of western Estonia contain only twelve species-level taxa assigned to nine genera, this fauna is one of the four richest Pridoli faunas known.